Evaluasi Kinerja Guru Penjasorkes Berdasarkan Kompetensi Profesional dan Kompetensi Sosial Pada SD Se-Kecamatan Tobu - Tafuy, Ardi Y. (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Teacher performance, professional competence, social competence of teacher penjasorkes elementary school in sub-district Tobu very low. This study aims to (1) describe the performance (2) describe professional competence (3) describe the social competence of teacher penjasorkes. This study uses qualitative methods of naturalistic results of principal interviews, teacher penjasorkes, learners, and the community. Source of data taken from school documents related to learning of penjasorkes (1) Performance of teacher penjasorkes at elementary school as sub-district Tobu still low because not mastering teaching materials, managing teaching program, not yet able to process class, using learning media (2) Professional competence in teacher The elementary school supervisor of Tobu sub-district is low this is seen from the educational background of low-ranking teacher of pemasorkes, has not understood the mastery of technology, has a good personality, be a good example, has not mastered the curriculum, and teachers who teach penjasorkes there are derived from different bikes. (3) The social competence of the elementary school teacher in Tobu sub-district is also low, the penjasorkes teacher has established cooperative relationship with various parties but it is necessary to keep the action and speech so that it is not considered by the public, the teacher of Penjasorkes in Tobu sub-district is considered less educational because Often consume alcoholic beverages. Conclusions of performance, professional competence, social competence of teacher penjasorkes not yet implemented maximally need to be renewed so that teacher penjasorkes itself can achieve performance and competence.